Cocoa pod husk wastes derived biochar for overcoming potassium deficiency in organic agriculture - Murali Gopal; Elain Apshara S.; Sathyaseelan Neenu; Alka Gupta (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Potassium (K) deficiency is emerging as a significant global agricultural challenge impacting 20% of farming areas and posing a threat to food security. In India, the potassium deficit has aggravated due to a focus on nitrogen and phosphorus application, with the net potassium balance declining from -3.29 million tonnes in 2000–01 to -7.2 million tonnes in 2015–16. Cocoa cultivation in Southern states of India like Kerala, Karnataka, Andhra Pradesh, and Tamil Nadu, produce substantial biomass waste, including cocoa pod husks, which are rich in potassium.